Relationship between Mental Health and Academic Achievement of Adolescent Students in Kolkata District, West Bengal - Chowdhury, Debdutta Pal (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The paper aims at analysing the impact of mental health on academic achievement of adolescent students of Kolkata. Mental health is the most important aspect of well-being of human. Adolescence is the most crucial & formative phase of human life where good mental health is very important for a balanced lifestyle for present and future. The researcher selected 100 sample of adolescent students giving representation to gender (Boys/Girls) and type of school (Private/Government) they belong. The Mental Health Inventory developed by Jagadish and Srivastav (1983) was used as the tool to measure the mental health status of the students. The academic achievement score of those students were also collected from the schools of Kolkata. Collected data were analysed with the help of Mean, Standard Deviation, t-test and Pearson’s Product Moment Correlation. The result revealed that there is a positive correlation between the mental health and academic achievement of adolescent students of Kolkata district. The study also found that there is no significant difference between adolescent girls and boys regarding mental health. But there is significant difference between adolescent girls and boys regarding academic achievement in Kolkata district. There is no significant difference between private and government school adolescent students regarding mental health. But there is significant difference between private and government school adolescent students regarding academic achievement in Kolkata district.